Quantitative analysis of mental and spiritual policy texts relevant for aging well in China - Zhang, Liyan; Qin, Mingyang (Frontiers in Public Health, 2025)
The policies related to spiritual older adult care issued by the state since the 18th National Congress were selected as the research object, and a two-dimensional analysis framework composed of policy tools and policy objectives was established. Seventy-one policy documents were analyzed by the content analysis method, and 285 analysis units were frequency counted to analyze the value tendency and inherent deficiencies of the current spiritual older adult care policies in depth. The policy tool dimension is characterized by the uncoordinated internal structure of supply-type tools, the varying level of environment-type tools, and the relative shortage of demand-type tools, and there is a gap in the degree of policy emphasis in the policy objective dimension. In the light of the policy feedback theory, we explore the policy recommendations that are conducive to promoting the development of mental older adult care from the perspective of the resource effect, the explanatory effect, the evolutionary effect, and the learning effect in turn.